Lived experiences of Pagsalo among Filipino adults with Tagasalo personality Maricon G. Garcia. - Garcia, Maricon G.
This qualitative phenomenological study aimed to explore the lived experiences of pagsalo among Filipino adults with tagasalo personality. We examined their experiences using the Western concept of parentification as the basis for analysis in order to aid the scarcity of existing literature regarding the understudied phenomenon. The study has two phases. During the first phase, Filipino adults aged 18 years old and beyond (n = 35) were asked to answer the Tagasalo Personality Scale. Top scorers, deemed as individuals with tagasalo personality, were asked to participate in the second phase of the data gathering. The second phase included a semi-structured interview with five individuals that varied in terms of their sibling rank, sex, and age. Interpretative Phenomenological Analysis was used as a framework and as a tool for analyzing the transcripts. The results show three superordinate themes : (1) Genesis of Pagsalo, (2) Process of Pagsalo, and (3) Consequences of Pagsalo. The findings of this study provided additional knowledge on the process of pagsalo. We also highlight its association with the Western construct of parentification. Our research could provide empirical support for crafting programs and policies that can aid individuals who undergo the process of pagsalo.Keywords: pagsalo, tagasalo, parentification, Interpretative Phenomenological Analysis.